Islamic deposit insurance from Shari'ah perspective: special reference to Malaysia and Sudan - Osmani, Noor Mohammad (Asian Research Consortium, 2016)
In Islamic banking system various Shari'ah principles are used as underlying contracts to receive the deposits. Usually wadi'ah and qard hasan are used for the current and saving deposits, while mudarabah is used for investment deposits. However, the issue of insuring investment deposits contradicts with the principle of mudarabah, as in principle mudarib is not allowed to provide any guarantee for the principal and fixed return, though there is a different view contrary to this. Hence this paper intends to study and analyze this issue from Shari'ah perspective. This is a qualitative paper and methods followed are descriptive and analytical. The paper also critically examines the practices of Malaysia and Sudan because unlike others these two countries established Islamic deposit insurance scheme under a particular legal system managed by a deposit insurer owned by the government. The paper posits that for a viable Islamic banking system deposit insurance is crucial from both macro and micro perspective. Deposit insurance system is considered one of the significant components of financial safety net. It maintains the public confidence in the banking system and promotes financial stability which conforms to the Maqasid al-Shari'ah. The paper concludes that insuring Islamic deposits is admissible by third party established by the state or by central banks. In fact, there is no contravention of Shari'ah if Islamic banks collaborated in establishing an institution based on the principles of cooperation and takaful to protect the deposits, where each participating bank is both a guarantor and a guaranteed.